Evolution of plant δ1-pyrroline-5-carboxylate reductases from phylogenetic and structural perspectives - Forlani, Giuseppe; Makarova, Kira S.; Ruszkowski, Milosz; Bertazzini, Michele; Nocek, Boguslaw (Frontiers in Plant Science, 2015)
Proline plays a crucial role in cell growth and stress responses, and its accumulation is essential for the tolerance of adverse environmental conditions in plants. Two routes are used to biosynthesize proline in plants. The main route uses glutamate as a precursor, while in the other route proline is derived from arginine. The terminal step of both pathways, the conversion of δ1-pyrroline-5-carboxylate (P5C) to L-proline, is performed by P5C reductase (P5CR) using NADH or NADPH as a cofactor. Since P5CRs are important housekeeping enzymes, they are conserved across all domains of life and appear to be relatively unaffected throughout evolution. However, global analysis of these enzymes unveiled significant functional diversity in the preference for cofactors (NADPH vs. NADH), variation in metal dependence and the differences in the oligomeric state. In our study we investigated evolutionary patterns through phylogenetic and structural analysis of P5CR representatives from all kingdoms of life, with emphasis on the plant species. We also attempted to correlate local sequence/structure variation among the functionally and structurally characterized members of the family.